Long lasting inhibitors of the gastric H,K-ATPase - Shin, Jai Moo (2009)
Proton pump inhibitors (PPIs) are acid-activated prodrugs which covalently bind to the gastric H,K-ATPase on its luminal surface. Only active pumps can be inhibited. The short plasma residence time of current PPIs prevents inhibition of pumps synthesized or activated after the PPI has disappeared, limiting the degree of acid inhibition even with BID administration. PPIs with a longer residence time should improve acid control. Various K(+) competitive inhibitors of the pump are being developed (APAs or PCABs), with the advantage of complete inhibition of acid secretion independent of pump activity. Early data on these suggest that twice a day administration would improve acid control compared to PPIs.